Optimizing Nitric Acid Leaching Conditions for Ash and Potassium Reduction in Empty Fruit Bunches-Based Biomass Energy - Dwi Jaksana Megah Santosa; Dede Hermawan; Sukma Surya Kusumah; Deded Sarip Nawawi; Jajang Sutiawan (Journal of Sylva Indonesiana, 2026)
Oil palm empty fruit bunches (EFB) represent an abundant biomass waste in Indonesia with high potential as a solid biofuel. However, the high ash content and the presence of alkali metals such as potassium in EFB contribute to low combustion efficiency and increase the risks of fouling and slagging. This study aims to reduce the ash and potassium content in EFB-based biomass fuel through demineralization using nitric acid (HNO₃). Acid demineralization was conducted using various acid concentrations (1%, 3%, and 5%) and soaking durations (10, 30, and 60 minutes). The parameters analyzed include ash content, calorific value, potassium content, as well as proximate and ultimate analysis. The results indicate that demineralization using 1% nitric acid for 10 minutes is the optimum condition, successfully reducing the ash content from 7.93% to 3,43% and reduced potassium by 77% (0,087%- 0,02%). In addition, the fix carbon increased (16,11%-18,09%), sulfur decreased (0,115%-0,086%), and the calorific value increased to 4355,83 cal/g. This treatment also increased the carbon and hydrogen content while reducing sulfur content, thereby improving thermal quality and reducing emissions. Acid demineralization using low-concentration nitric acid is effective in reducing ash and potassium content, thereby enhancing the performance of EFB-based biopellets as a biomass energy source.